2017
DOI: 10.1007/s10460-017-9827-3
|View full text |Cite
|
Sign up to set email alerts
|

Do advisors perceive climate change as an agricultural risk? An in-depth examination of Midwestern U.S. Ag advisors’ views on drought, climate change, and risk management

Abstract: Through the lens of the Health Belief Model and Protection Motivation Theory, we analyzed interviews of 36 agricultural advisors in Indiana and Nebraska to understand their appraisals of climate change risk, related decision making processes and subsequent risk management advice to producers. Most advisors interviewed accept that weather events are a risk for US Midwestern agriculture; however, they are more concerned about tangible threats such as crop prices. There is not much concern about climate change am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 52 publications
(67 reference statements)
1
15
0
Order By: Relevance
“…Risk perception is critical as a driver of collective action for many human-environment issues, including climate change adaptation and mitigation (Church et al 2018;Shin and Choi 2015). Early studies indicated that risk perception was an important variable in models of climate change-related behaviors (O'Connor et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Risk perception is critical as a driver of collective action for many human-environment issues, including climate change adaptation and mitigation (Church et al 2018;Shin and Choi 2015). Early studies indicated that risk perception was an important variable in models of climate change-related behaviors (O'Connor et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have concluded that the climate change information generated by scientists must be made relevant to local contexts for farmers to find it useful [9][10][11][12][13][14]. Some [15] highlight the importance of taking farmer perspectives into account; they document how personal experiences with climate-related events inform risk perceptions and help determine adaptation actions among Vermont farmers.…”
Section: Perceptions Of Climate Change and Adaptation Strategiesmentioning
confidence: 99%
“…The agricultural sector is comprised of multiple stakeholder groups in addition to producers. How producers make decisions and find information is complex; for example, they use many sources of information for farm management decisions, including family, other producers, media sources, university and governmental sources, and crop advisors [ 19 , 20 ]. Considering the complexity of decision-making and multitude of information sources, we sought to answer the following questions: How do climate scientists communicate with agricultural stakeholder groups about climate science?…”
Section: Introductionmentioning
confidence: 99%